1993
DOI: 10.1038/jcbfm.1993.58
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Alzheimer's Disease: A Statistical Approach Using Positron Emission Tomographic Data

Abstract: Correlational analysis of regional cerebral glucose metabolism (rCMRglc) obtained by high-resolution positron emission tomography (PET) has demonstrated reduced neocortical rCMRglc interactions in mildly/moderately demented patients with probable Alzheimer's disease (AD). Thus, identification of individual differences in patterns of rCMRglc interactions may be important for the early detection of AD, particularly among individuals at greater risk for developing AD (e.g., those with a family history of AD). Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…This notion is supported by an extensive literature which reports that AD is characterized by reduced cerebral energy metabolism (8), impaired activities of the tricarboxylic acid cycle enzymes (25,121,162), and defects in the mitochondrial ETC (21,32,45,146,96,193). The most consistent defect at ETC level is the decline in cytochrome c oxidase (COX) activity, an effect that is positively correlated with Ab concentration, as determined by in vitro studies (30).…”
Section: Oxidative Stress In the Aging Brainsupporting
confidence: 53%
“…This notion is supported by an extensive literature which reports that AD is characterized by reduced cerebral energy metabolism (8), impaired activities of the tricarboxylic acid cycle enzymes (25,121,162), and defects in the mitochondrial ETC (21,32,45,146,96,193). The most consistent defect at ETC level is the decline in cytochrome c oxidase (COX) activity, an effect that is positively correlated with Ab concentration, as determined by in vitro studies (30).…”
Section: Oxidative Stress In the Aging Brainsupporting
confidence: 53%
“…Other investigators have utilized multivariate analytic techniques to distinguish AD from control subjects (Azari et al, 1993;Grady et al, 2001) and to predict conversion to AD (Johnson et al, 1998). In a Tc-HMPAO SPECT study, the pattern derived from multivariate analysis showed 84.4% accuracy in discriminating 27 questionable dementia patients who did not progress from 18 questionable dementia subjects who converted to AD during 2 years of follow-up (Johnson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Using the visual semiquantitative method, sensitivity was 92%, specificity was 83%, and accuracy was 87% (Azari et al, 1993;Burdette et al, 1996;Fazekas et al, 1989;Kippenhan et al, 1992;Scheurich et al, 2005). Quantitative methods showed that overall sensitivity was 94%, specificity was 87%, and accuracy was 91% (Duara et al, 1989;Herholz et al, 1990Herholz et al, , 1993Ishii et al, 2006;Kawachi et al, 2006;Mielke et al, 1994;Minoshima et al, 1995;Mosconi et al, 2005;Ng et al, 2007;Ohyama et al, 2000;Szelies et al, 1994;von Borczyskowski et al, 2006).…”
Section: Distinctive Abnormal Pattern and Possible Causesmentioning
confidence: 99%